ANALISIS KAIDAH TAJWID DALAM PELAFALAN HADIS PADA SELEKSI TILAWATIL QUR’AN/HADIS (STQH): KAJIAN DESKRIPTIF-KRITIS - Ana, Zumrotus Sholikatun Nurjanah (Jurnal Studi Islam, 2024)
Abstract: The implementation of Tajweed rules in the recitation of hadiths during the Qur’an/Hadith Recitation Competition (STQH) is the focus of this research. STQH, organized by the Ministry of Religious Affairs, is a biennial competition that has included a category for hadith memorization since 2019. The competition consists of two subcategories: 100 hadiths with a chain of narrators (sanad) and 500 hadiths without a complete chain of narrators. However, the application of Tajweed rules in the recitation of hadiths has sparked controversy. Some argue that since hadiths and the Qur’an are distinct, Tajweed rules should not be applied uniformly. Scholars hold differing opinions on the matter, with some supporting the use of Tajweed rules based on hadiths containing the Prophet’s supplications and the Arab tradition of employing Tajweed. Others express concerns about potential similarities between the recitation of hadiths and the Qur’an. This research aims to provide a comprehensive understanding of the implementation of Tajweed rules in the recitation of hadiths during STQH, contributing to the development of the competition and addressing the differing perspectives surrounding the use of Tajweed rules in hadith recitation. Key words: tajweed, hadits, STQH, differing opinions.